Water Use for Seepage-Irrigated Pepper with Plastic Mulch in Florida - Sanjay Shukla; Niroj Shrestha; Fouad H. Jaber (EDIS, 2014)
Bell pepper (Capsicum annuum) is an important crop for Florida and accounts for a significant fraction of its agricultural water use. Most of it is produced in south Florida, where the water table is shallow. Seepage irrigation is one of the most common systems used in south Florida for growing plastic-mulched vegetable crops, including bell pepper. Compared with an open field production, covering the soil with impermeable plastic reduces soil evaporation and increases transpiration. This 3-page fact sheet summarizes the results from a crop water use study for the seepage-irrigated pepper in south Florida. Written by Sanjay Shukla, Niroj Shrestha, and Fouad H. Jaber, and published by the UF Department of Agricultural and Biological Engineering, August 2014.